Accelerated versus conventional beef production and processing - Dikeman, Michael E.; Nagele, K.N.; Myers, S.M.; Schalles, R.R.; Kropf, Donald H.; Kastner, Curtis L.; Russo, F.A. (American Society of Animal Science, 2008)
Twenty-four 8-mo-old Angus X Hereford (A X H) reciprocal crossbred steers and 28 3/8 Simmental X 1/4 Chianina X 3/8 Angus or Hereford steers (S X C) were utilized to study two production systems and two carcass-processing systems. One-half of each type was allotted by weight (257.6 kg average) to either an accelerated (ACC) or conventional (CONV) production system. The ACC system consisted of feeding an 85% concentrate diet for 140 d to A X H cattle and for 180 d to S X C cattle. The CONV system included backgrounding on prairie hay and sorghum grain for 140 d (A X H) and 183 d (S X C) before finishing on an 82% concentrate diet (116 d for A X H and 122 d for S X C). The ACC system resulted in lower (P<.05) metabolizable energy to gain ratios (ME/G) and lower costs of gain. Cattle on the ACC system were slaughtered younger and at lighter weights (P<.05) and had lower (P<.05) yield grades and quality grades than CONV cattle. The S X C-ACC cattle had a lower (P<.05) ME/G and tended to have a lower cost of gain than A X H-ACC cattle. The S X C cattle had lower (P<.05) yield grades and higher (P<.05) percentages of carcass tissue water than A X H cattle. The S X C cattle had lower (P<.05) quality grades than A X H cattle. The ACC system resulted in higher (P<.05) longissimus (LD) and semimembranosus (SM) tenderness scores than the CONV system and equal flavor and juiciness scores. Economic analyses suggest that S X C-ACe cattle had the lowest break-even live price and lowest cost/kg retail product. The S X C-CONV cattle tended to have the highest break-even live price, whereas A X H-CONV cattle had the highest cost/kg retail product. The Ace processing involved electrical stimulation (ES) of each carcass right side at 1 h postmortem for 2 rain with 400 V, 1 amp and a frequency of 60 Hz. At 2 h posmaortem the inside round and boneless shortloin were hot-boned (HB) and chilled 6 d at 2 to 4 C. The control (C) side was chilled 48 h, boned, and muscles stored 4 d at 2 to 4 C. The ESHB resulted in slightly (P>.05) faster LD pH declines. The ESHB LD steaks had higher (P<.05) juiciness scores, but were not different in flavor or tenderness compared with C steaks. The ESHB treatment resulted in higher (P<.05) SM shear values and lower (P<.05) sensory-panel tenderness scores than those of C. The LD display-color scores did not differ (P>.05) between ESHB and C treatments. The combination of S X C cattle and ACC production was more attractive economically than CONV production of A X H cattle.
Keywords: Food science; Performance; Carcasses; Nutrition; Palatability; Electrical treatment; Boning